Master track of HEINCKE cruise HE668 in 1 sec resolution (zipped, 2 MB) - Ingo Schewe (PANGAEA, 2025)
Raw data acquired by position sensors on board RV Heincke during expedition HE668 were processed to receive a validated master track which can be used as reference of further expedition data. During HE668 the inertial navigation system IXSEA PHINS III and the GPS receivers Trimble Marine SPS461 and SAAB R5 SUPREME NAV were used as navigation sensors. Data were downloaded from DAVIS SHIP data base (https://dship.awi.de) with a resolution of 1 sec. Processed data are provided as a master track with 1 sec resolution derived from the position sensors extquotesingle data selected by priority and a generalized track with a reduced set of the most significant positions of the master track.